2019
DOI: 10.1002/cncr.32364
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnosis aspirin use, DNA methylation, and mortality after breast cancer: A population‐based study

Abstract: BACKGROUND:The authors hypothesized that epigenetic changes may help to clarify the underlying biologic mechanism linking aspirin use to breast cancer prognosis. To the authors' knowledge, this is the first epidemiologic study to examine whether global methylation and/or tumor promoter methylation of breast cancer-related genes interact with aspirin use to impact mortality after breast cancer. METHODS: Prediagnosis aspirin use was assessed through in-person interviews within a population-based cohort of 1508 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Our findings are in accordance with previous studies suggesting that epigenetic modifications are involved in the chemopreventive actions of aspirin. Recently, an association between aspirin use and BRCA1 promoter methylation that affects the mortality after breast cancer has been shown [ 26 ]. Similarly, in mouse inflammation model, aspirin has been shown to reduced tumor multiplicity by suppressing histone deacetylases (HDAC), with concomitant increase of H3K27ac in the promoter regions of pro-inflammatory genes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with previous studies suggesting that epigenetic modifications are involved in the chemopreventive actions of aspirin. Recently, an association between aspirin use and BRCA1 promoter methylation that affects the mortality after breast cancer has been shown [ 26 ]. Similarly, in mouse inflammation model, aspirin has been shown to reduced tumor multiplicity by suppressing histone deacetylases (HDAC), with concomitant increase of H3K27ac in the promoter regions of pro-inflammatory genes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory properties of aspirin exert favorable effects on managing the challenges of survivorship in various cancers [ 15 , 16 , 17 ]. A prolongation of survival among aspirin users was seen across different tumor types, such as colorectal, gastrointestinal, and other cancers [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In addition, several retrospective studies demonstrated that cancer patients who have taken aspirin might be at a lower risk of developing metastatic cancer [ 21 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several retrospective studies demonstrated that cancer patients who have taken aspirin might be at a lower risk of developing metastatic cancer [ 21 , 27 ]. Nevertheless, despite the growing number of randomized controlled trials and meta-analyses of these studies that demonstrate the benefits of aspirin in various cancers [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], the effect of aspirin on NPC has not been explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the latest global cancer statistics, there was almost 2.1 million newly diagnosed breast cancer patients in 2018, amount to nearly one forth women cancer cases [1]. In the wake of the progress of the era, there has been numerous advanced innovations been exploiting in the early diagnosis and the systematical management of BRCA [4]. Nevertheless, patients with BRCA are still facing a formidable challenge in the light of their undesirable overall survival.…”
Section: Introductionmentioning
confidence: 99%